Dose response test of patient-derived cancer organoids to irradiation - Yu, Haina; Lin, Canfeng; Chen, Fan; Chen, Lifeng; Liu, Weizhen; Liu, Hualong; Li, Jing; Yao, Ye (Frontiers in Oncology, 2025)
BackgroundPatient-derived cancer organoids emerged as an innovative model in basic and translational medicine research, as well as precision medicine. However, most radiation oncologists are still unaware of the value of organoids in radiation oncology research, especially in precision radiation oncology. The methods for assessing organoid cell death after irradiation are also undefined.MethodsThree organoid lines were successfully established from the surgical specimens of rectal cancer patients. Genetic characterization of rectal cancer organoids was conducted. The survival of rectal cancer organoids after X rays irradiation was evaluated by image-based analysis and cell counting kit-8.ResultsThe three organoid lines displayed diverse architecture and captured heterogeneity of the tumors. The most frequently mutated genes and pathways among rectal cancer tumors also presented in rectal cancer organoids. Image-based analysis validated organoid survival after X rays irradiation, while cell counting kit-8 failed. The survival curves from imaging analysis were more representative, with an initial linear slope, followed by a shoulder, and tending to become straight again. This was the first study to investigate the appropriate testing method of using organoids to study cancer radiosensitivity.ConclusionCancer organoids were easy to use for the research of radiobiology of cancer. Image-based analysis is more accurate than cell viability (tested by cell counting kit-8) for studying cancer radiosensitivity via organoids.